REPLACEMENT AND CANCELLATION OF CLAIM SECURITY MEASURES IN ECONOMIC PROCEEDINGS - Khlivnyi, Yaroslav (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose: to describe the features of replacing and canceling measures of counterclaim protection in the economic process, based on the analysis of which to propose ways to improve them. Research methods: the method of analysis is used to study judicial practice and identify problems of claim enforcement. The formal-logical method was used to form conclusions, proposals aimed at improving economic procedural legislation regarding the replacement and cancellation of measures to counter- ensure a claim in an economic process. Results: it is proved that the application of measures to ensure the claim, as well as their cancellation or change, must be justified and confirmed by evidence. The circumstances of the court case may change during its consideration, as new evidence may appear or a dispute may be settled between the parties, precisely because of these reasons, the continuation of the application of security measures loses its necessity. Moreover, there are circumstances when the continuation of the enforcement measure would violate the rights and interests of the applicant. Therefore, when applying measures to secure a claim, the court must proceed from the actual circumstances of the case and change or cancel them in accordance with the circumstances of the case that arise during the consideration of the case. Discussion: features of replacing measures to secure a claim in the course of court proceedings. Grounds and procedure for canceling measures to secure a claim. Current judicial practice in the context of replacement or cancellation of measures to secure a claim in an economic process.